The perception of parents toward quality of child centre in Malaysia / Nur Adriana Johan…[et.al] - Johan, Nur Adriana; Wan Mohd Noor, Wan Hanis Marini; Mohd Lazin, Mohd Aslan Aiman; Hasnan, Wan Hazwan Fikri (Faculty of Communication & Media Studies, 2019)
Child care center is the care and supervision of a child or multiple children at a time, whose ages range from six weeks to thirteen years old. Child care is the action or skill of looking after children by a day-care center, babysitter, nannies, teachers or other providers. This discuss the features which are predictive of child care quality in improving laws and policies of child care protection in Malaysia. Firstly, this prove the importance of high quality child care towards the children development. The cases of children maltreatments happening around the country are alarming. A recent case involves a child who was severely burnt due to the negligence of the child care provider. For instance, the victim was awarded RM 403 018.74 as compensation (Wahid, 2016). These are just one example of the cases which were reported. It is believed that there are more cases that go unreported due to various reasons. This studies on the importance of having high quality child care in ensuring the good growth of the children is discussed.